Iran and Israel Cyber Warfare and Interference of US - Muhammad Umar (Social Science Review Archives, 2025)
The Israeli-Iranian struggle has also gone to the cyber battle space of cyber warfare. This matches the reality of evolving global power competition, in which states increasingly use cyberspace to achieve strategic ends, with the relative anonymity and reduced physical risk involved. At the heart of this cyberwar is a history of power struggle rooted in geopolitical competition, religious ideologue, and national security imperatives. Israel and Iran have engaged in a relentless back-and-forth of cyberattacks and counterattacks that have targeted critical infrastructure, security apparatuses and government services, proving both countries consider cyber the dominant theatre in their competition for dominance. One of the most serious cyberattacks was the deployment of the Stuxnet virus in 2010, made with the high technical cooperation between the United States and Israel. Stuxnet was built to sabotage Iran’s uranium enrichment centrifuges at the Natanz plant by causing them to physically degrade. It was, at the time, the first publicly known cyberattack to inflict physical damage in the physical world, a perilous practice of precedent for digital-age international relations. It showed not only the power of state-directed cyber war, but also how deeply America had invested in Israel’s cyber campaigns against Iran. Iran has drastically improved its cyber warfare program since then, and has targeted Israeli infrastructure, including an attempt to poison water sources, paralyze the public transit system and hack government websites. Israel has responded with its own cyberattacks, like one that temporarily shut down Iran’s Shahid Rajaee port operations, as well as others that targeted fuel distribution networks and surveillance systems. These countermeasures have created a resilient and a volatile digital battlefield span the Middle East. The US has a complex and important role to play in this cyber war. The claim based on Israelis’ use of American cyber offensive technology is, however, entirely unfounded, as the US is Israel’s closest ally and co-developer of offensive cyber capabilities, who enables and aids Israeli efforts to curb Iran's technological and nuclear ambition. American intelligence agencies and military cyberunits cooperate closely with their Israeli counterparts, sharing information, offering technological know-how and providing operational support, when needed. At the same time, the U.S. is also locked in confrontations with Iran, manifested in Iranian-backed cyberattacks against U.S. banks, oil companies and government agencies. These copycats of cyber tensions have also more deeply drawn the U.S. into the Israel-Iran cyber battle. In spite of the extensive use of cyber tools, there is still no established international law framework to govern cyber war, prompting concerns about responsibility, proportionality and escalation. Enter the Israel-Iran war and we can see how fraught with problems it is to use cyber means for political reasons—especially when the infrastructure to be hit is civilian. Moreover, the cyber warfare raises (or seems to) bigger questions about global inequities in technology; about the role of secrecy and surveillance in the age of cyberpower; and about the defense-offense continuum within the cyber domain. In short, the Israel-Iran cyber war, helped along by an actively involved U.S., constitutes a new world of global conflict, in some ways mirroring the new necessities of civilian life, in which the digital is the foremost player in national security and geopolitics. It emphasizes the imperative for global norms and ethical limits in the fast-changing sphere of cyber war.